Research on mechanical properties of steel-polypropylene fiber concrete and application of beam structure - Li, Jiuyang; Luo, Jingwei; Chen, Li; Fan, Xinmei; Zhu, Yuepeng; Wang, Xiaoyu; Guo, Jingpeng (Frontiers in Materials, 2024)
Concrete faces the difficulties of low tensile strength and poor crack resistance in building structures. In order to remedy this deficiency. In this paper, steel-polypropylene hybrid fiber reinforced concrete (SPFRC) was prepared by adding steel fiber (SF) and three kinds of polypropylene fiber (PF) to C50-grade concrete. The mechanical properties and microstructure of SPFRC were studied with different fiber combinations and content, obtaining the best hybrid combination. Based on this, the bending resistance and cracking of SPFRC beam members were investigated. The results demonstrate that the addition of fiber improves the compressive strength of ordinary concrete by 0.16% ∼ 17.69%, the splitting tensile strength by 15.18% ∼ 47.45%, and the bending strength by 3.54% ∼ 26.77%. Compared with single-fiber concrete, the hybrid fiber can achieve better internal microstructure, which further enhances the mechanical properties of the material. Hybrid fibers overlap within concrete beams, effectively redistributing stress and inhibiting the formation and propagation of cracks. For the three types of SPFRC beams, the cracking load is increased by 14.29% ∼ 28.57% compared with PC beam, the ultimate bearing capacity is increased by 9.68% ∼ 19.35%. The optimal dosage is determined as 1.0% SF, 0.6% Embossed polypropylene fiber (PBF). It provides reference for the application of SPFRC in flexural members.